2014
DOI: 10.3109/09513590.2014.976546
|View full text |Cite
|
Sign up to set email alerts
|

The impact of body mass on inflammatory markers and insulin resistance in polycystic ovary syndrome

Abstract: In the PCOS group, the levels of CRP and IR were elevated, compared to their counterparts, regardless of body mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 27 publications
0
21
1
Order By: Relevance
“…Several studies in the literature have evaluated changes in the inflammatory state in PCOS and documented an increase in CRP levels regardless of the BMI in patients with PCOS [1,3,8,9,20]. In the present study, levels of CRP were increased both in obese and lean patients with PCOS compared with the obese and lean controls.…”
Section: Discussioncontrasting
confidence: 35%
See 1 more Smart Citation
“…Several studies in the literature have evaluated changes in the inflammatory state in PCOS and documented an increase in CRP levels regardless of the BMI in patients with PCOS [1,3,8,9,20]. In the present study, levels of CRP were increased both in obese and lean patients with PCOS compared with the obese and lean controls.…”
Section: Discussioncontrasting
confidence: 35%
“…On the other hand, there is an ongoing debate as to which mediators may be increased in patients with PCOS. For instance, previous studies have documented increased levels of C-reactive protein (CRP) in patients with PCOS in support of this argument [1,8,9]. Imbalances between proinflammatory such as tumor necrosis factor a (TNF-a) and anti-inflammatory cytokines are argued to have an impact on PCOS [10].…”
Section: Introductionmentioning
confidence: 86%
“…The pathophysiology of PCOS is heterogeneous and remains unresolved. However, in the PCOS pathogenesis the pivotal role of hyperinsulinemia and insulin resistance (IR) is highlighted [2,5,6]. IR is a factor linking PCOS and metabolic syndrome (MS).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies suggest that chronic infections are followed by increased levels of reactive oxygen species, myeloperoxidase, oxidative stress, in ammatory cytokines (such as IL-6 and TNF-α), high-sensitivity C-reactive protein (hs-CRP), adhesion molecules, and blood lymphocytes and monocytes, a process which plays an important role in the etiology and pathogenesis of PCOS. This cascade of pro-in ammatory incidents is proposed as a potential link between periodontal disease and PCOS (20)(21)(22). In a study, that examined the levels of anti-in ammatory cytokines in gingival crevicular uid (GCF), saliva and serum of women with PCOS and healthy women, it was shown that PCOS and gingivitis are synergistic with increased levels of IL-6 and TNF-α.16 (22).…”
Section: Introductionmentioning
confidence: 99%
“…This cascade of pro-in ammatory incidents is proposed as a potential link between periodontal disease and PCOS (20)(21)(22). In a study, that examined the levels of anti-in ammatory cytokines in gingival crevicular uid (GCF), saliva and serum of women with PCOS and healthy women, it was shown that PCOS and gingivitis are synergistic with increased levels of IL-6 and TNF-α.16 (22). In another study, the level of matrix metalloproteinase-8 in the saliva and serum of patients with periodontal disease and PCOS showed an increase compared to the healthy controls (17).…”
Section: Introductionmentioning
confidence: 99%